API for beginners : JavaScript and getting started with APIs and AJAX - Svekis, Laurence (Packt Publishing, 2019)
"Explore using JavaScript XHR and fetch to connect to multiple web API endpoints retrieve JSON data and update HTML. Access several popular web APIs and retrieve response content for web applications. This course covers how to make AJAX requests using the XMLHttpRequest within JavaScript as well as fetch. JavaScript code knowledge is a prerequisite for the course. Scope of this course is focused on using JavaScript to connect to web APIs."--Resource description page